Can the United States Expand Apprenticeship? Lessons from Experience - Robert I. Lerman (Institute for the Study of Labor (IZA), 2012)
Can expanded apprenticeship reduce the concerns about the U.S. workforce? The U.S. labor market faces a rise in unemployment rates, sharp declines in the employed share of U.S. adults, extremely high youth unemployment, high wage inequality, and low or stagnant wage growth for workers below the BA degree. Currently, the primary solution advanced by policymakers helping more people go to college is both expensive and of limited effectiveness. Unfortunately, the U.S. policy debate is rarely informed by international experience with systems that prepare young people for careers, especially for technical occupations. Few if any cite the experience in Germany, Switzerland, and Austria in achieving high levels of income and relatively low levels of earnings inequality without a college graduation rate above the OECD average. Americans know little about the success of apprenticeship systems abroad nor are they or their political leaders aware of the growth of apprenticeship programs in Australia, England, and other advanced economies. Given the potential for expanded apprenticeship to deal effectively with skill mismatches, wage inequality, declines in manufacturing employment, and high youth unemployment, why has the U.S. failed to mount a significant apprenticeship initiative? A number of reports, including the Organization for Economic Development and Cooperation (OECD 2009) review of youth employment, have recommended expanding apprenticeship training yet failed to stimulate significant action. Apprenticeship training would seem consistent with American values of pragmatism and extensive use of the market and public-private collaborations, and a limited role for government. The paper begins by describing the existing U.S. apprenticeship system, how the system evolved, and measures of its effectiveness. The next sections examine the multiple barriers to expanding apprenticeship in the U.S., highlighting both ideological and practical obstacles. The final section describes how best to take advantage of the opportunities for expansion.
Keywords: J24; J08; I28; 330; apprenticeship; skills; training; Betriebliche Ausbildung; Berufsbildungspolitik; USA